Straight into darkness - Kellerman, Faye (New York : Warner Books, 2005)
A homicide inspector in 1920s Munich hunts for a serial killer"--Provided by the publisher.
Keywords: Police -- Fiction. -- Germany -- Munich; Serial murders -- Fiction; Large type books; Fiction; Jewish fiction; Domestic fiction; Historical fiction; War stories